Flexural behaviour of RC one-way slabs reinforced using PAN based carbon textile grid - Abd, Suhad M.; Ibrahim, Amer M.; Hussein, Omar H.; Shamim, Saba; Qaidi, Shaker; Najm, Hadee Mohammed; Özkılıç, Yasin O.; Sabri Sabri, Mohanad Muayad (Frontiers in Materials, 2023)
Textile reinforced mortar (TRM) is mainly used for strengthening of existing structural members whereas, on the other hand Textile reinforced concrete (TRC) is a technology implied in construction of new members for enhancing the structural behaviour. Application of TRM on the tension zone of the reinforced concrete (RC) slabs to improve the flexural capacity has been investigated by many researchers in the past. However, the effectiveness of textile fabrics, used as internal reinforcement in the RC slab (TRC technology) needs to be studied. The paper, therefore, presents the experimental research conducted on three one-way RC slabs specimens reinforced using textile grid. An innovative Polyacrylonitrile (PAN) based carbon textile grid was used as internal reinforcement in combination with the steel bars. Two textile-reinforced RC slabs having one and two layers of textile grid (SRC + 1T and SRC + 2T respectively) and one reference slab (SRC) was fabricated to investigate the flexural behaviour under a four-point loading system. The internal textile reinforcement layer(s) was con-firmed to be effective, particularly in terms of improving the cracking load, ductility, deformability and toughness. The material ductility of SRC + 1T and SRC + 2T slabs were increased by 41% and 44% compared to SRC slab. Also, the deformability ratio was found to be greater than 4, indicating a ductile failure of textile-reinforced slabs. Further, based on the load-deflection relation, mo-ment-curvature curves were derived. Moreover, these curves were also developed using Eurocode 2 prediction model. The experimental and the predicted moment-curvature curves showed good agreement.